The formulation of epistemological disjunctivism - French, Craig (Wiley, 2016)
I argue that we should question the orthodox way of thinking about epistemological disjunctivism. I suggest that we can formulate epistemological disjunctivism in terms of states of seeing things as opposed to states of seeing that p. Not only does this alternati ve formulation capture the core aspects of epistemological disjunctivism as standardly formulated, it has two salient advantages. First, it avoids a crucial problem that arises for a standard formulation of epistemological disjunctivism—the basis problem. And second, it is less committed than standard formulations are in the metaphysics of perception.